DIVERSIFICATION OF MEDIA CONTENT IN RUSSIAN MEDIA COMPANIES: THE EXAMPLE OF RBC HOLDING, GAZPROM-MEDIA AND NATIONAL MEDIA GROUP - A. I. Karpova (Вестник Кемеровского государственного университета, 2015)
The paper is devoted to the problem of content diversification in Russian media holdings and contains applied research. Through the case-method (the example of Russian companies “RBC”, “Gazprom-Media” and “National Media Group”) the author examines how the latest digital technology makes media companies repackage their product and submit tit simultaneously in different media. The aim of the study is to identify the degree of diversification of content and mutual integration of the media within media holdings. As a result the author describes three models of diversification of content, which could be also used by the media managers in their work.